ANALISIS PERAMALAN ARIMA BOX-JENKINS PADA DATA PENGIRIMAN BARANG - Anik Rufaidah; Muhamad Afif Effindi (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2017)
In the world of forecasting industry needs to be done to see the results that will come so that all the needs that can be prepared dipelukan. On the delivery of this data is made forecasting that will be used to provide services to customers related to the required fleet. In the industrial world there is often an uncertain fluctuation, which is due to several factors that can, among others, due to seasonal events resulting in spikes at certain times. So to predict the delivery of goods to come, which is used to prepare the number of fleets that must be prepared in this research is PT. AML is engaged in the expedition, which is the delivery of goods in this study we use the delivery of goods with trucking. And the result of the analysis is the result of the estimated value of MA (0,1,1) which got the estimated value model . For residual analysis already meet the test results.Keywords: Forecasting, ARIMA.